MORPHOFUNTIONAL ESTIMATION OF NEIROPROTECTRIVE ACTIVITY OF HUMULUS LUPULUS L., EXTRACT AT THE CHRONIC EMOTIONAL STRESS - Ya. G. Razuvaeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
In experiments on white rats (Wistar line) it was found that the dry extract of Humulus lupulus L possessed neiroprotectrive activity at the chronic emotional stress. It was normalized white rats brain morphofuntinal status.